Accelerated aging and characterization of HDPE pin type insulators (15 kV). Issue 9 (November 2021) - Erbetta, Cynthia DC; Silva, Maria Elisa SR; Freitas, Roberto FS; Sousa, Ricardo G
The study of the behavior of polymeric material used for insulators in the electrical system is extremely important in order to evaluate their lifetime as well as their performance when exposed to different environmental conditions. In the present work, the behavior of high-density polyethylene (HDPE) pin type insulators (15 kV), under accelerated aging conditions, was studied. Samples were exposed to aging, for 200 h, 1000 h, and 2000 h, in accelerated weathering chambers, according to two different methods. In Method 1, the parameters were established based on natural aging in location conditions, and in Method 2, ASTM G155 standard parameters were used. All samples were characterized by rheometry, Fourier-transform infrared spectroscopy (FTIR), and differential scanning calorimetry (DSC). The accelerated aging conditions, used in Methods 1 and 2, affected the aging of HDPE pin type insulators samples differently, the changes being more intense in Method 1.